2012
DOI: 10.1029/2011gb004168
|View full text |Cite
|
Sign up to set email alerts
|

The dark portion of the Mediterranean Sea is a bioreactor of organic matter cycling

Abstract: [1] Total prokaryotic abundance, prokaryotic heterotrophic production and enzymatic activities were investigated in epi-, meso-and bathypelagic waters along a longitudinal transect covering the entire Mediterranean Sea. The prokaryotic production and enzymatic activities in deep waters were among the highest reported worldwide at similar depths, indicating that the peculiar physico-chemical characteristics of the Mediterranean Sea, characterized by warm temperatures (typically 13 C also at abyssal depths), sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
54
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 96 publications
14
54
1
Order By: Relevance
“…We found that DNase activities, even when normalized to cell abundance, were higher in the sediments of La Medee than in the oxic sediments outside the anoxic basin. Conversely, aminopeptidase, b-glucosidase and alkaline phosphatase activities (used as a proxy for potential mobilization of proteins, carbohydrates and organophosphate monoesters) [54] were up to one order of magnitude lower in La Medee than in oxic sediments. We cannot exclude the possibility that the measured rates might be influenced by sediment decompression [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…We found that DNase activities, even when normalized to cell abundance, were higher in the sediments of La Medee than in the oxic sediments outside the anoxic basin. Conversely, aminopeptidase, b-glucosidase and alkaline phosphatase activities (used as a proxy for potential mobilization of proteins, carbohydrates and organophosphate monoesters) [54] were up to one order of magnitude lower in La Medee than in oxic sediments. We cannot exclude the possibility that the measured rates might be influenced by sediment decompression [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, mesopelagic fish biomass appears to be comparatively high based on the characteristics of the deepscattering layer, from which fish biomass has been modelled (Proud et al, 2017). With regard to microbes, the metabolic activity of prokaryotes appears to be higher for mesopelagic Mediterranean populations compared with those found at similar depths in other systems, related possibly to the relatively warm temperature of the deep waters, 13 C (Luna et al, 2012). Also, the abundances of typical bacterivores, heterotrophic nanoflagellates, appear to be low relative to abundances of prokaryotes compared with other systems perhaps because of high ciliate concentrations (Aristegui et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the faster recycling of organic P and organic N back into the dissolved inorganic pools in the Western Mediterranean Sea. Evidence for this faster recycling of organic matter can be seen in the higher population densities of bacteria observed in the Western Mediterranean Sea, which are four to six times greater than in the Eastern Mediterranean Sea, as well as the higher concentrations of alkaline phosphatase, which are about three times greater than in the Eastern Mediterranean Sea [21]. Alkaline phosphatases are a group of enzymes that are designed to break the chemical bonds that hold P locked into organic compounds, thereby releasing dissolved phosphate to seawater.…”
Section: Primary Productivity and Nutrient Cycling: West-east Differementioning
confidence: 88%